Testing ASICs with multiple identical cores. - Yuejian Wu (IEEE Transactions on computer-aided design of integrated circuits and systems)
Predesigned cores and reusable modules are popularly used in the design of large and complex application specific integrated circuits (ASICs). As the size and complexity of ASICs increase, the test effort, including test development effort, test data volume, and test application time, has also significantly increased. This paper shows that this test effort increase can be minimized for ASICs that consist of multiple identical cores. A novel design for testability (DFT) technique is proposed to test ASICs with identical embedded cores. The proposed technique significantly reduces test application time, test data volume, and test generation effort.